1991
DOI: 10.1111/j.1365-2826.1991.tb00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor Binding in Female Prairie Voles: Endogenous and Exogenous Oestradiol Stimulation

Abstract: Previous studies have demonstrated that oxytocin receptors in specific nuclei of rat forebrain are regulated by gonadal steroids. The current study used in vitro receptor autoradiography to investigate the distribution and regulation of oxytocin receptors in the forebrain of the female prairie vole (Microtus ochrogaster). In contrast to rats, in female prairie voles gonadal steroid secretion and oestrus behaviour result from male chemosignal stimulation and ovulation is induced by mating. Thus, the prairie vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 23 publications
0
56
1
Order By: Relevance
“…There is considerable evidence from between species comparisons that monogamous and nonmonogamous mammals have differences in the distribution of peptide receptors including those for OT and AVP (Witt et al, 1991;Shapiro and Insel, 1992;Insel et al, 1994). In addition, we have observed that early manipulations of OT, even at the lowest dose used here (1 mg/ kg), are capable of producing life-long, sexually-dimorphic changes in peptide receptors (Bales et al, 2007b) .…”
Section: Discussionmentioning
confidence: 60%
“…There is considerable evidence from between species comparisons that monogamous and nonmonogamous mammals have differences in the distribution of peptide receptors including those for OT and AVP (Witt et al, 1991;Shapiro and Insel, 1992;Insel et al, 1994). In addition, we have observed that early manipulations of OT, even at the lowest dose used here (1 mg/ kg), are capable of producing life-long, sexually-dimorphic changes in peptide receptors (Bales et al, 2007b) .…”
Section: Discussionmentioning
confidence: 60%
“…Given the sexually dimorphic nature of this AVP pathway (Bamshad et al, 1993;Wang, 1995;Wang et al, 1996b) and lack of similar changes in AVP activity in female voles , these data provide correlational evidence of the potential involvement of central AVP in physiological and behavioral processes associated with mating and pair bond formation in male prairie voles (Bamshad et al, 1994;Wang et al, 1994;Wang et al, 1998). In female prairie voles, exposure to male chemosensory cues induced an increase in OTR binding in the anterior olfactory nucleus (Witt et al, 1991), indicating that social behavior can also affect OTRs.…”
Section: Neuropeptidergic Regulation Of Social Attachmentmentioning
confidence: 70%
“…or i.p.) do not facilitate sexual receptivity in female prairie voles pretreated with E (Witt et al , 1990), and treatment with an Oxt antagonist does not inhibit sexual behavior (Witt et al , 1991). However, in sexually-naĂŻve females (no exposure to males after weaning), daily Oxt injection (s.c.) for 5 days increases the likelihood of mating (compared to saline treated females), and treatment of Oxt with E increases sexual receptivity greater than E alone (Cushing and Carter, 1999).…”
Section: Behaviormentioning
confidence: 99%